1986
DOI: 10.1002/j.1556-6978.1986.tb00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Supervision in Groups

Abstract: In this study, the authors organized group supervision behaviors into categories that represent requirements of effective group supervision. T o determine the requirements for effective supervision in groups, the authors collected reports of behaviors exhibited by a physician and a behavioral scientist acting as co-supervisors. These reports were gathered from 84 2nd-year medical students participating in a practicum designed to improve their patient interviewing skills. The 84 reports of effective supervisory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In fact, there is little evidence reported here and in Ellis and Dell to suggest that counselor trainees and supervisors differ in the core dimensions (map) of supervision. These findings appear to be at variance with evidence that (a) more than 12 dimensions were necessary to account for supervisees’ or supervisors’ perceptions of supervision (Reising & Daniels, 1983; Savickas et al, 1986; Worthington, 1984), (b) premaster’s trainees and predoctoral trainees significantly differed in their perceptions of supervision (Heppner & Roehlke, 1984; Reising & Daniels, 1983; Worthington & Stern, 1985), (c) counselor trainees’ perceptions of supervision did not match supervisors’ perceptions (Heppner & Roehlke, 1984; Worthington & Stern, 1985), and (d) supervision (and perceptions thereof) were found to differ significantly from one academic setting to another (Worthington, 1984). Although the reasons for these discrepancies were not conspicuous, one plausible explanation lies in the types of data collected and analysis from the two studies reported here (i.e., paired comparisons and MDS).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In fact, there is little evidence reported here and in Ellis and Dell to suggest that counselor trainees and supervisors differ in the core dimensions (map) of supervision. These findings appear to be at variance with evidence that (a) more than 12 dimensions were necessary to account for supervisees’ or supervisors’ perceptions of supervision (Reising & Daniels, 1983; Savickas et al, 1986; Worthington, 1984), (b) premaster’s trainees and predoctoral trainees significantly differed in their perceptions of supervision (Heppner & Roehlke, 1984; Reising & Daniels, 1983; Worthington & Stern, 1985), (c) counselor trainees’ perceptions of supervision did not match supervisors’ perceptions (Heppner & Roehlke, 1984; Worthington & Stern, 1985), and (d) supervision (and perceptions thereof) were found to differ significantly from one academic setting to another (Worthington, 1984). Although the reasons for these discrepancies were not conspicuous, one plausible explanation lies in the types of data collected and analysis from the two studies reported here (i.e., paired comparisons and MDS).…”
Section: Discussionmentioning
confidence: 60%
“…A few researchers have attempted to identify the salient variables or dimensions of supervision (Ellis & Dell, 1986; Reising & Daniels, 1983; Savickas, Marquart, & Supinski, 1986; Worthington, 1984; Worthington & Roehlke, 1979). Worthington and Roehlke (1979) factor analyzed 42 supervisor behaviors rated by neophyte counselor trainees and retained two factors (i.e., Evaluation and Support).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Less attention has been given to negative aspects of group supervision, including factors that might hinder supervisees' learning. The literature that exists suggests that personality conflicts may disrupt the group's flow and functioning, taking time away from the supervision of cases (Counselman & Gumpert, 1993); group members may avoid giving constructive criticism to one another (Tebb, Manning, & Klaumann, 1996); critical responses by other group members to the member who is presenting a case may be detrimental to learning by causing shame, embarrassment, and anxiety (Altfeld, 1999); the large amount of feedback gleaned by the presenting therapist might be too overwhelming (Altfeld, 1999); group pressure to conform might stifle individual creativity (Kadushin, 1985); the supervisor may not have the skill to manage the complexities of group supervision (Kadushin, 1985; Tebb et al, 1996); and supervisors may resort to unhelpful storytelling or the reporting of irrelevant experiences (Savickas, Marquart, & Supinski, 1986).…”
mentioning
confidence: 99%
“…Graves and Graves (1973) found that students in group supervision who were rated as giving the most meaningful feedback were more verbal and gave more positive and “owned” feedback than students who were rated as giving less meaningful feedback. Savickas, Marquart, and Supinski (1986) found that trainees in supervision groups rated giving encouraging feedback as one of the most effective supervisor behaviors. Starling and Baker (2000), in a qualitative study of four group supervisees, found that peer feedback was noted as especially important.…”
mentioning
confidence: 99%